Enhanced recovery (fast-track surgery) after total ankle replacement: The state of the art. Issue 8 (December 2022) - Querci, Lorenzo; Caravelli, Silvio; Di Ponte, Marco; Fuiano, Mario; De Blasiis, Paolo; Sirico, Felice; Baiardi, Annalisa; Zannoni, Francesca; Mosca, Massimiliano
Abstract: The post-operative results of a total ankle replacement are not determined solely by an optimal surgical technique, but by an appropriate anesthesiological and rehabilitative post-operative approach. Enhanced functional recovery often depends on a multidisciplinary approach based on a correct framework of the patient and his needs, requests, and characteristics. Extensive bibliographical research has been performed on Pubmed, Google Scholar, Scopus. This comprehensive and inclusive review of the literature aims to examine the state of the art of "fast-track" protocols employed in total ankle replacement (TAR), considering pre-operative preparation, anesthetic management, intraoperative and surgical factors, post-operative rehabilitative care and reduction of hospitalization time.